Mozart directing his Requiem - Munkácsy, Mihály, 1844-1900 (artist):::Creator:::::::::::: (D. Appleton & Co.; New York; United States)
Depiction of Mozart conducting his Requiem Mass, printed from the photogravure by Goupil & Cie.